Pericapsular Nerve Group (PENG) Block as Opioid-Sparing Postoperative Analgesia in a Geriatric Patient Undergoing Cemented Hip Hemiarthroplasty with Traumatic Intracerebral Hemorrhage and Right Bundle Branch Block: A Case Report - Sugeng Budi Santoso; Septian Adi Permana; Algi Iskandar (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Postoperative pain control in geriatric hip-fracture patients is challenging, and the challenge is magnified when neurological and cardiovascular comorbidities restrict the safe use of systemic opioids. Opioids, the analgesic standard, carry risks of respiratory depression, sedation, and hemodynamic instability that are particularly hazardous after intracranial hemorrhage and in cardiac conduction disease. The pericapsular nerve group (PENG) block is a sensory-selective, motor-sparing regional technique that may reconcile effective analgesia with these constraints. Case presentation: A 64-year-old man presented after a 2-meter fall with a displaced closed right intertrochanteric femoral fracture (Boyd-Griffin II), minimal traumatic intracerebral hemorrhage (right frontal lobe, ICH score 0), and electrocardiographic right bundle branch block (RBBB). He was classified ASA III and underwent cemented hip hemiarthroplasty under general endotracheal anesthesia. A multimodal, opioid-minimizing strategy centered on an ultrasound-guided PENG block combined with intravenous paracetamol was implemented. Analgesia was effective, systemic opioid requirements were minimized, the Glasgow Coma Scale remained E4V5M6, and hemodynamic and neurological parameters stayed stable throughout the high-care postoperative period. Conclusion: In a high-risk geriatric patient in whom opioids threatened both neuromonitoring and cardiac stability, a PENG block-centered multimodal regimen delivered reliable analgesia while preserving neurological assessability and hemodynamic stability. The PENG block is a safe, practical regional option for complex hip-fracture surgery and merits prospective study in comparably comorbid populations.